2008
DOI: 10.1007/s00125-008-0941-z
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section is associated with an increased risk of childhood-onset type 1 diabetes mellitus: a meta-analysis of observational studies

Abstract: Aims/hypothesis The aim of this study was to investigate the evidence of an increased risk of childhood-onset type 1 diabetes in children born by Caesarean section by systematically reviewing the published literature and performing a meta-analysis with adjustment for recognised confounders. Methods After MEDLINE, Web of Science and EMBASE searches, crude ORs and 95% CIs for type 1 diabetes in children born by Caesarean section were calculated from the data reported in each study. Authors were contacted to Diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
355
6
20

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(392 citation statements)
references
References 50 publications
11
355
6
20
Order By: Relevance
“…However, other epidemiological studies did not report higher rates of asthma, diabetes type 1, obesity, and inflammatory bowel disease for children born with birth interventions 12, 16. Several studies that included meta‐analyses reported that children born by cesarean delivery were at higher risk of developing obesity, diabetes, or asthma in childhood 4, 6, 30, 31…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other epidemiological studies did not report higher rates of asthma, diabetes type 1, obesity, and inflammatory bowel disease for children born with birth interventions 12, 16. Several studies that included meta‐analyses reported that children born by cesarean delivery were at higher risk of developing obesity, diabetes, or asthma in childhood 4, 6, 30, 31…”
Section: Discussionmentioning
confidence: 99%
“…Short‐term adverse health outcomes included jaundice, feeding problems, and hypothermia and often are part of the adaptation of the infant to being outside the uterus 7, 27, 28. The longer‐term adverse health outcomes included asthma, respiratory infections (eg, common cold, pneumonia, bronchitis), gastrointestinal disorders, other infections (eg, sepsis, streptococcus, cystitis), metabolic disorder (eg, hypoglycemia, neonatal diabetes mellitus, diabetes mellitus type 1 or 2, localized adiposity), and eczema, based on the potential effect that mode of birth has on immune‐related diseases 5, 6, 7, 12, 13, 14, 15, 16, 17, 18. An overview of all adverse health outcomes and other covariates with corresponding ICD‐10‐AM codes are presented in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 C-section can also compromise future pregnancies, and have long term negative effects for the newborns, such as obesity, asthma, type-1 diabetes, and lead to unexplained stillbirths in the second pregnancy. 2,[6][7][8][9][10][11][12] These risks explain why c-section on demand is considered, "an expensive and dangerous luxury". 13 Current evidence strongly advises against unnecessary c-sections.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have linked alterations in the intestinal microbiota composition with conditions such as obesity (Ley et al, , 2005Murphy et al, 2010;Turnbaugh et al, 2006), inflammatory bowel disease (Greenblum et al, 2012), colitis (Bellavia et al, 2013;Klimesova et al, 2013) and T1D Murri et al, 2013;Roesch et al, 2009). Moreover, risk of T1D onset in childhood is higher in children delivered by Caesarean section (Cardwell et al, 2008), where there is also altered microbiota composition (Dominguez-Bello et al, 2010). Previous studies have examined the role of the intestinal microbiota in the development of T1D but these are often limited due to the models used [i.e.…”
Section: Introductionmentioning
confidence: 99%